Optimizing Recruitment of Black Adolescents into Behavioral Research: A Multi-Center Study. (11th February 2021) - Ellis, Deborah A; Rhind, Jillian; Carcone, April Idalski; Evans, Meredyth; Weissberg-Benchell, Jill; Buggs-Saxton, Colleen; Boucher-Berry, Claudia; Miller, Jennifer L; Al Wazeer, Mouhammad; Drossos, Tina; Dekelbab, Bassem
Abstract: Objectives: Adolescents of color are underrepresented in behavioral health research. Study aims were to quantify the amount and types of outreach effort needed to recruit young Black adolescents with type 1 diabetes and their primary caregiver into a clinical trial evaluating a parenting intervention and to determine if degree of recruitment difficulty was related to demographic, diabetes-related, or family characteristics. Methods: Data were drawn from a multi-center clinical trial. Participants ( N = 155) were recruited from seven pediatric diabetes clinics. Contact log data were used to quantify both number/type of contacts prior to study enrollment as well as length of time to enrollment. Families were coded as having expedited recruitment (ER) or prolonged recruitment (PR). Baseline study data were used to compare ER and PR families on sociodemographic factors, adolescent diabetes management and health status and family characteristics such as household organization and family conflict. Results: Mean length of time to recruit was 6.6 months and mean number of recruitment contacts was 10.3. Thirty-nine percent of the sample were characterized as PR. These families required even higher levels of effort (mean of 9.9 months to recruit and 15.4 contacts). There were no significant between-group differences on any baseline variable for ER and PR families, with the exception of family income. Conclusions: Researchers need to make persistent efforts in order to successfully enroll adolescents of color and their caregivers into clinical trials. Social determinants of health such as family resources may differentiate families with prolonged recruitment within such samples.